Response of common bean (Phaseolus vulgaris L.) to nitrogen, phosphorus and rhizobia inoculation across variable soils in Zimbabwe - Chekanai, V.; Chikowo, Regis; Vanlauwe, Bernard (Elsevier, 2018)
Common bean is an important crop with potential to curb malnutrition in poor Sub-Saharan African populations. Yields of common bean (Phaseolus vulgaris L.) are, however poor, limited by low soil phosphorus (P), nitrogen (N) and poor biological N2-fixation. On-farm experiments were carried out to study the effect of N, P and rhizobia inoculation on common bean yield and yield components during the 2014/2015 and 2015/2016 cropping seasons in Eastern Zimbabwe. Experiments were conducted on five farmers’ fields located in two agroecologies; three fields were considered to be degraded with soil organic carbon (SOC) < 4 g kg−1 and available P < 6 mg kg−1, while the two non–degraded sites had SOC > 7 g kg−1 and available P > 15 mg kg−1. Two common bean varieties (Gloria and NUA45) were tested in a split-plot arranged in randomized complete block design. The main plot factor was the combination of N (0 and 40 kg ha−1) and P (0 and 20 kg ha−1), and the sub-plot factors were variety (Gloria and NUA 45) and inoculation with Rhizobium tropici strain CIAT899 (+/− inoculum). At planting, both N and P were applied at 20 kg ha−1, with an additional 20 kg ha−1 N top dressing applied at flowering. Analysis of variance indicated common bean did not respond to rhizobia inoculation (P > 0.05) whilst P significantly increased the number of nodules and active nodules per plant (P < 0.001), and grain yield. Application of 40 kg ha−1 N significantly increased the number of pods per plant, number of seeds per pod, and grain yields. A significant NP interaction was only observed on grain yield for non-degraded soils. Co-application of N and P in non-degraded sites increased grain yields from 0.27 to 1.48 Mg ha−1during the first season and from 0.37 to 2.09 Mg ha−1during the second season. On degraded sites, NP application resulted in uninspiring grain yield gains of 0.09 to 0.19 Mg ha−1 during the first season, and from 0.16 to 0.28 Mg ha−1 in the second season. In general, effects of N or P were not significantly different, suggesting that farmers could invest in either of these nutrients for increased common bean grain yields. Strategically, P investments would be more logical as residual P effects to rotational cereals improve overall cropping system performance. The response of common bean to inoculation in Zimbabwe still needs to be widely investigated for these and other varieties.